Integrated Healthcare Delivery Models: A Comprehensive Review Of Clinical, Public Health, And Allied Medical Services (The Review of Diabetic Studies, 2024)
Healthcare systems worldwide continue to face challenges related to fragmented service delivery, resulting in gaps in care continuity, inefficiencies, and suboptimal health outcomes. Integrated healthcare delivery models have emerged as a strategic approach to enhance coordination across clinical services, public health systems, and allied medical disciplines. This comprehensive review aims to synthesize existing evidence on integrated healthcare delivery models and examine how collaboration among clinical, public health, and allied medical services contributes to improved patient outcomes, system efficiency, and population health. A structured literature review was conducted across major academic databases, focusing on studies published in recent years that address multidisciplinary integration, organizational coordination, and system-level enablers. The findings highlight that effective integration is associated with improved continuity of care, enhanced preventive and population health services, reduced duplication of efforts, and better patient safety and satisfaction. Key enabling factors include interprofessional collaboration, supportive governance structures, workforce readiness, and digital health infrastructure. This review underscores the importance of adopting comprehensive, system-wide integration strategies to address complex healthcare needs and strengthen healthcare system resilience. The findings provide valuable insights for policymakers, healthcare leaders, and researchers seeking to advance integrated healthcare delivery across diverse healthcare settings.